THE EFFECT OF REPRESENTATIVENESS, AVAILABILITY, ANCHORING, RISK PERCEPTION, AND HERDING ON INVESTMENT DECISIONS SYARIAH INVESTORS - Rico Priandana Loris; Prabowo Yudo Jayanto (UNIB Press, 2021)
Investors do not always think rationally but sometimes think irrational. Decision-making based on irrational thinking is influenced by a psychological bias which often leads to wrong decisions. This study aims to find empirical evidence of the influence of representativeness, availability, anchoring, risk perception, and herding on the investment decisions of sharia investors who open stock accounts at Phintraco Sekuritas Semarang. The population in this study were investors who have opened Islamic stock accounts at Phintraco Sekuritas Semarang. The sample is respondents who have opened Islamic stock accounts at Phintraco Sekuritas Semarang. The sampling technique used was simple random sampling and data collection techniques used a questionnaire. The data were analyzed using descriptive analysis and Structural Equation Modeling (SEM). The results showed that representativeness, anchoring, risk perception, and herding have a significant positive effect on the investment decisions of Islamic investors. Meanwhile, the availability variable does not affect investment decisions in Islamic investors.